Pressure Neutralization in Surgical Management of Chronic Subdural Hematoma: An Enhancing Patient Safety Technique - Elnaggar, Mohamed Ahmed; Elkholy, Hany; Eissa, Mohamed K.; Elnoamany, Hossam; Elnoamany, Nour; Elsanafiry, Mohamed Said Mohamed (Indian Journal of Neurotrauma, 2025)
Background Chronic subdural hematoma (CSDH) is a common neurosurgical condition, often presenting with progressive neurological deficits. Surgical evacuation via burr hole craniotomy is a standard treatment. This study evaluates the pressure neutralization technique for gradual decompression using wide bore cannula before dural opening.Materials and Methods This retrospective study included 81 patients with CSDH and previous history of head trauma who underwent gradual decompression using wide bore cannula before dural opening. Preoperative, intraoperative, and postoperative parameters were evaluated.Results The mean patient age was 67 ± 8.7 years, with a male predominance (69.1%). The most common presenting symptoms were hemiparesis (70.4%) and headache (29.6%). Hematoma was predominantly left-sided (61.7%) with a mean thickness of 2.46 ± 0.5 cm. Midline shift exceeded 10 mm in 63.0% of cases preoperatively. Postoperatively, Glasgow Coma Scale improved to 14.84 ± 0.37, with clinical improvement in 77.8% of patients showing resolution of weakness. Midline shift resolved at 76.5%, and residual hematoma was minimal in 16%. The average hospital stay was 4.2 ± 1.3 days, and only one patient (1.2%) underwent postoperative wound infection.Conclusion Gradual decompression using wide bore cannula before dural opening is highly effective in managing CSDH, leading to significant clinical and radiological improvement with minimal complications. Radiological findings, particularly hematoma thickness and midline shift, are reliable indicators of surgical efficacy and patient recovery.
Keywords: chronic subdural hematoma; burr hole craniotomy; midline shift; hematoma evacuation; neurosurgery